PERFORMANCE ANALYSIS OF CERAMIC INSULATOR WITH RTV SILICONE RUBBER COATING FOR COASTAL AREA APPLICATION. CASE STUDY: PANGANDARAN COASTAL AREA - FAUZIAH (NIM: 23215091), DINI
This study analyzed the effect of Room Temperature Vulcanized (RTV) silicone rubber coating on ceramic pin post insulator performance of 20 kV for use in tropical coastal area. The test was conducted at Pangandaran Switchyard Area, by giving natural aging for five years seven months since first installing at October 2011 until last measurement at Mei 2017 to six ceramic insulators with coating and six ceramic isolators without coating. During aging time the insulators are given stress by AC voltage 50 Hz of 11 KV. During aging, data have been taken periodically in the form of leakage current data, contact angle, THD, and surface temperatur of the insulator. Data retrieval was conducted three times, ie morning afternoon and evening because the average humidity and temperature in each condition has different characteristics so that it can be known on what condition isolator flashover experience are easily obtained. From the data in the form of leakage current wave can then be determined the harmonic components for further analysis of the insulator characteristics. After both types of insulators have aged for 5 years 7 months, researchers conducted a test to determine the performance of the insulator in the condition of clean fog and salt fog with the increase in voltage. From the result, along clean fog testing both insulators did not experience flashover. While in the test with salt fog, non-coating insulator experience flashover at 50 kV voltage and coated insulator have higher flashover voltage that is 60 kV. To find out changed parameters during aging, simulations are performed on the measurement data in the field parameters are amplitude, waveform and THD of leakage current insulators during aging. Based on the test results, it is found that the use of coatings can increase performance of the ceramic insulator.